Original articleβ-amyloid deposits in veins in patients with cerebral amyloid angiopathy and intracerebral haemorrhage - Mendel, Tadeusz; Wierzba-Bobrowicz, Teresa; Stępień, Tomasz; Szpak, Grażyna Maria (Folia Neuropathologica, 2013)
Aim of the study: To review the incidence and grade of cerebral amyloid angiopathy (CAA) in veins in patients who died due to spontaneous intracerebral haemorrhage (ICH). Material and methods : Neuropathological examinations were performed in the study group of 189 patients. Cerebral amyloid angiopathy was diagnosed according to the Boston criteria and confirmed during an autopsy. The Vonsattel and Mountjoy scales were used to assess the grade and scores of CAA. Results : In the study group composed of 189 ICH patients, 42 presented CAA. In the microscopic examination, of the 42 patients 33 (78%) showed β-amyloid deposits in veins, which makes 17% of the total group of patients with ICH. In this group, the age ranged from 54 to 97 (mean age 80.18 ± 8.15 years). A group of 33 (27 women and 6 men) patients comprised 15 (45%) patients with severe CAA, 13 (40%) with moderate and 5 (15%) with mild CAA classified according to the Vonsattel scale. According to the Mountjoy scale 28 (85%) patients had a score of 4, which indicated the total involvement of the vessel. Conclusions : β-amyloid deposits in veins were found in 78% of patients with CAA and ICH, which makes 17% of the total group of patients with ICH. Interestingly, β-amyloid deposits in veins are not so rare in patients with CAA who died due to intracerebral haemorrhage. Cerebral amyloid angiopathy localization in the veins of the brain was observed more frequently than previously suspected. Veins may play a role in the elimination of β-amyloid from the brain.